1987
DOI: 10.1111/j.1398-9995.1987.tb00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with Hymenoptera venoms

Abstract: Immunotherapy with Hymenoptera venoms is widely used throughout the world and is accepted as an effective treatment for most patients with Hymenoptera venom allergy. There are, however, still some unresolved problems with this form of treatment. At present there is no definite test which makes it possible to identify patients at risk ‐ and thus candidates for immunotherapy ‐ unequivocally. On the basis of prospective studies on the natural history of Hymenoptera allergy, venom immunotherapy is indicated in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(15 citation statements)
references
References 64 publications
(71 reference statements)
0
13
0
2
Order By: Relevance
“…True double sensitization and also cross-reactivity must be considered as causes of the double positivity in this group of patients [1]. Cross-reactivity of venom hyaluronidases and with carbohydrate epitopes is known [2,3], and distinguishing between double sensitization and cross-reactivity is crucial in the choice of allergen for specific immunotherapy in patients who did not recognize the culprit insect [4]. If double sensitization is proven, immunotherapy with both venoms is required; if cross-reactivity is the case, only the venom that caused sensitization should be used [1].…”
Section: Introductionmentioning
confidence: 99%
“…True double sensitization and also cross-reactivity must be considered as causes of the double positivity in this group of patients [1]. Cross-reactivity of venom hyaluronidases and with carbohydrate epitopes is known [2,3], and distinguishing between double sensitization and cross-reactivity is crucial in the choice of allergen for specific immunotherapy in patients who did not recognize the culprit insect [4]. If double sensitization is proven, immunotherapy with both venoms is required; if cross-reactivity is the case, only the venom that caused sensitization should be used [1].…”
Section: Introductionmentioning
confidence: 99%
“…Controlled studies have shown efficacy in patients with allergic rhinitis/conjunctivitis, allergic asthma, and allergic reactions from stinging insects (1,2). Effective treatment is correlated with the use of standardized vaccines in maintenance doses containing 5-20 g of major allergen for 3-5 years (3).…”
mentioning
confidence: 99%
“…Unfortunately, VIT may be associated with a risk of adverse events [7]. We have found that side effects during VIT are quite frequent (reported by 43.8% of patients in our cohort).…”
Section: Discussionmentioning
confidence: 56%
“…As a consequence, a limited access to this life-saving procedure may be seen. What is striking, a high level of variations (0–46%) and inconsistency in the side-effects frequency is reported in the literature [710]. Moreover, there are just a few comprehensive studies dedicated to this topic [1116].…”
Section: Introductionmentioning
confidence: 99%